Earnings Non‐Synchronicity and Voluntary Disclosure - Gong, Guojin; Li, Laura Yue; Zhou, Ling (Contemporary Accounting Research, 2013)
Earnings non‐synchronicity reflects the extent to which firm‐specific factors determine a firm's earnings. Prior research suggests that high earnings non‐synchronicity impedes corporate outsiders' ability to process information. This study examines the impact of earnings non‐synchronicity on managers' decisions to provide earnings forecasts. We propose that high earnings non‐synchronicity motivates managers to issue earnings forecasts to reduce information asymmetry between managers and investors and to preempt costly information acquisition by outsiders. Consistently, we find a positive relation between earnings non‐synchronicity and managers' propensity to issue earnings forecasts, particularly long‐horizon forecasts. This positive relation is weaker when earnings are easier to predict based on the firm's earnings history and is stronger when the firm has higher institutional ownership and greater analyst following. We also find that the market's reaction to management forecasts increases with earnings non‐synchronicity. Overall, the evidence suggests that managers voluntarily provide earnings forecasts to alleviate the adverse consequences of earnings non‐synchronicity. These findings provide a more complete picture about the impact of earnings non‐synchronicity on a firm's information environment, and highlight the effect of the nature of information asymmetry on voluntary disclosures.